Altered DLPFC-hippocampus connectivity during working memory: independent replication and disorder specificity of a putative genetic risk phenotype for schizophrenia - Schneider, Michael; Mößnang, Carolin Ulrike; Schäfer, Axel; Dixson, Luanna; Meyer-Lindenberg, Andreas; Tost, Heike (Schizophrenia bulletin, 2017)
Abstract. Altered connectivity of dorsolateral prefrontal cortex (DLPFC) and hippocampus during working memory is considered an intermediate phenotype for schizophrenia